Comparison of short term results between closing the peritoneum and not closing it during cesarean section (Latakia University Journal -Medical Sciences Series, 2025)
Background: Cesarean section is a life saving procedure in the field of obstetrics  , but its associated with an increased risk of complications .studies showed that the method of closing the abdominal wall may affect these complications .this study aim to compare the short term results of closing the peritoneum and not closing it during the cesarean section.Materials and methods: This study was conducted as a prospective m randomized , controlled , clinical study in Tishreen university ,department of  gynecology and obstetrics , latakia .between March 2023 and March 2024.The study included 150 pregnant women who under went elective lower cesarean section for the first time. The women were randomly distributed into two groups. The first group consisted of 75 patients which the abdominal muscles and the parietal and visceral peritoneum were closed , while in the second group of 75 patient also m the muscles and the peritoneum were not closed . the steps of the operation and the type of sutures used were standardized. The preventive protocol using antibiotics and analgesics was applied similarly . The short term results were evaluated in both groups (duration of the surgery , occurrence of nausea and vomiting, infection of the wound m return of the intestines to normal movements m temperature  m need for blood transfusion and type and quantity of the analgesics after surgery . the data was analyzed statistically using the SPSS system.Results: We found significant increase in the duration of the surgery (p-value